Onion production technology for kharif onion - Khade, Yogesh P; Thangasamy, A; Gorrepati, Kalyani (Indian Horticulture, 2019)
To get maximum benefit of high prices, farmers need to enhance their productivity for onion production. This can be achieved by selection of suitable kharif onion cultivars, timely sowing of nursery and transplanting of seedlings, proper management of plant diseases and weed population. Techniques developed for kharif onion production at ICAR-Directorate of Onion and Garlic Research, Rajgurunagar could be used to enhance productivity.